Uric Acid Values Along with Doppler Sonography Findings as a Tool for Preeclampsia Screening - Medjedovic, Edin; Suljevic, Alma; Iglica, Amer; Rama, Admir; Mahmutbegovic, Emir; Muftic, Amela; Dzihic, Ema (Medical archives (Sarajevo, Bosnia and Herzegovina), 2019)
Preeclampsia is defined as hypertension (systolic pressure ≥140 mmHg or diastolic pressure ≥90 mmHg) after week 20 of gestation with one or more of the following symptoms: proteinuria, organ dysfunction (including renal, hepatologic, hematologic or neurological complications) and in case of stagnation of fetal development. So far, there are no valid clinical tools or tests that can tell with sufficient sensitivity and specificity in early pregnancy which pregnant woman will develop preeclampsia or have unwanted outcomes. To present the properties of biochemical parameter, uric acid, in patients with signs of preclampsia, which was confirmed by Doppler sonography. The study included 60 female subjects in the second trimester of pregnancy who were examined or were hospitalized at the Clinic of Gynecology and Obstetrics, Clinical Center University of Sarajevo. Pregnant women who had normal Doppler sonography scan of the uterine arteries in the second trimester of pregnancy were included in the control group, while pregnant women with pathologic Doppler sonographic findings in the second trimester of pregnancy were included in the group of pregnant women at risk of preeclampsia, i.e. the study group. There is statistically significant difference between the average value of uric acid in the control and in the study group (213.36 ± 28.96 μmol / L vs 249.73 ± 47.06 μmol / L) (F = 12.991; p = 0.001). Applying the Wilcoxon non-parametric paired test to the average uric acid values during all measurements within the control group, no statistically significant difference was found. There was a statistically significant increase in the study group between all measurements, from 18.04 μmol / L between the first and second measurement (Z = -1.955; p = 0.043), 29.10 μmol / L between the second and third measurement (Z = -2.973; p = 0.003), 37.27 μmol / L between the third and fourth measurement (Z = -4.325; p = 0.001) and 109.87 μmol / L at the end of the study in comparison to values from the start of the study (Z = -4.309; p = 0.001). Uric acid values should become part of a broad biochemical range in screening and optimizing the treatment of patients diagnosed with early preeclampsia.